Testing a teacher costs to caring resilience model to identify burnout mediators. (June 2023) - Brown, Sherry Pineau; Biddle, Catharine
Abstract: The purpose of this study was to understand the extent to which teachers experience costs to caring (e.g. secondary traumatic stress, burnout, and intent to leave the profession) and to test a Teacher Costs to Caring Resilience Model (TCCRM) using structural equation modeling. Participants consisted of 542 teachers in the Northeastern U.S. Findings suggested that the personal protective factors of resilience and compassion satisfaction showed a negative direct effect on costs to caring. Further, the professional protective factor of working in a positive school climate showed a negative indirect effect specifically on burnout. Focusing on improving teacher resilience, compassion satisfaction, and school climate using a systems-based approach modeled on the TCCRM is suggested.